G59 The international collaborative infantile spasms study (iciss) comparing hormonal therapies (prednisolone or tetracosactide depot) and vigabatrin versus hormonal therapies alone in the treatment of infantile spasms: early clinical outcome. (27th April 2015) - O'Callaghan, F; Edwards, S; Hancock, E; Johnson, A; Kennedy, C; Lux, A; Mackay, M; Newton, R; Nolan, M; Rating, D; Schmitt, B; Verity, C; et al.
Abstract : Infantile spasms (IS) are a serious epileptic encephalopathy that occur most commonly between 2 and 14 months. The spasms occur in association with hypsarrhythmia or similar on EEG. There is often coincident psychomotor arrest or regression. Between March 2007 and May 2014, infants with IS and a compatible EEG were enrolled in a multicenter treatment trial. Participating countries were the UK, Germany, Switzerland, Australia and New Zealand. Infants were randomised to receive either hormonal therapy and vigabatrin or hormonal therapy alone. A second stage randomization allowed hormonal treatment to be allocated as either prednisolone or tetracosactide depot. Minimum doses were: vigabatrin 100 mg/kg/day, prednisolone 40 mg per day, or IM tetracosactide depot 0.5 mg on alternate days. Hormonal treatment was continued for 2 weeks and then weaned over 2 weeks. Vigabatrin was continued for 3 months and then weaned over a month. The early primary outcome measure was cessation of spasms on and between days 14 and 42. Analysis is by intention to treat. 377 children were enrolled and early clinical outcome data will be available on 376 (1 case withdrew). 186 were allocated hormonal therapy and vigabatrin and 191 were allocated hormonal therapy alone. We will report on the primary clinical outcome and serious adverse clinical events. Developmental outcome at 18 months of age will be reported in a subsequent paper. To date this is by far the largest treatment study of infantile spasms ever undertaken.